Introduction Displacement, Memory and the Visual Arts: Second-Generation (Jewish) Artists. Issue 1 (1st March 2023) - Wiltshire, Imogen; Louwagie, Fransiska
Abstract: This introduction explains the origins, aims and scope of this thematic issue on Displacement, Memory and the Visual Arts: Second-Generation (Jewish) Artists, which builds on a symposium held at the University of Leicester in May 2021. It offers a discussion of key perspectives on the notions of 'second generation' and 'postmemory' within the visual arts, followed by an overview of the contributions to the publication. The article then identifies and analyses a number of key threads and themes in the volume, including issues of belated memory, the uses by artists of archival images and documents, their engagement with space and embodiment, and the role of art in memory transmission. These discussions serve as a basis for an examination of how postmemory in the visual arts opens up possibilities for considering the relationships of second-generation artists to the past, and, more widely, revisiting contemporary understanding and remembrances of the Holocaust and its aftermath.